755 nm alexandrite laser for the reduction of tumor burden in basal cell Nevus syndrome - Tannous, Zeina (2011)
Background and Objective Basal Cell Nevus syndrome (BCNS) is characterized by numerous basal cell carcinomas (BCCs). Multiple treatments with the pulsed dye laser (PDL) have been shown, in small studies, to be effective for the treatment of superficial and nodular BCCs. Like PDL, the alexandrite laser can be vessel-selective, but has the added advantage of deeper tissue penetration. We evaluated the utility of the alexandrite laser in reducing the tumor burden in BCNS with a single treatment. Study Design/Materials and Methods A case report and review of the literature are presented. A 45-year-old man with BCNS and a history of radiation therapy presented with an extraordinarily high tumor burden (>250 BCCs). As a compassionate measure to reduce the tumor burden, we investigated the utility of a single treatment of the long-pulsed 755 nm alexandrite laser to several BCC lesions. The treated lesions were evaluated at 2-month and 7-month clinical follow-up. Histopathologic analysis of a treated lesion was performed at 7-month clinical follow-up. Results At 2-month, and 7-month clinical follow-up, 15 of 18 treated lesions or about 83% of the alexandrite laser treated lesions showed a complete clinical response and appeared as hypopigmented areas with scarring. Histopathologic analysis of a treated lesion at 7-month clinical follow-up showed no evidence of residual tumor. Conclusions The long-pulsed alexandrite laser may be helpful in significantly reducing tumor burden in difficult to manage BCNS patients with a single treatment. This provides a facile and practical treatment alternative for the management of challenging cases of BCNS. The limitation of this study is that it is a single case observation. Larger, prospective studies are needed to confirm these observations. Lasers Surg. Med. 42:68–71, 2011 © 2011 Wiley-Liss, Inc